Supporting deprescribing in long-term care: An approach using stakeholder engagement, behavioural science and implementation planning - Lisa M. McCarthy; Barbara Farrell; Pam Howell; Tammie Quast (Elsevier, 2022)
Approaches for optimizing medication use and enhancing medication experiences, including deprescribing, for older people living in long-term care homes are urgently needed. Through a multiphase initiative involving an environmental scan (2018) and two stakeholder forums (2019, 2020), we created a framework for developing and implementing sustainable deprescribing practices in this sector. Representatives from public advocacy, health care professionals, long-term care, pharmacy service providers, and regional health and public policy organizations in Ontario, Canada were consulted. We used behavioural science and implementation planning strategies to develop four target behaviours and 14 supporting actions; five of these actions were prioritized for further work. Throughout the phases, stakeholders committed to participation at various levels including ongoing implementation teams working to develop resources for the prioritized actions. A key element of success was attracting and sustaining engagement of a wide variety of relevant stakeholders from across the health system by leveraging best practices in stakeholder engagement. The approach used is described in detail so that it can be adapted and applied by others to plan large behaviour change initiatives.